IMPLIKASI INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING PRODUK BUNGA SEGAR PADA UMKM “ILOMATA” TOMOHON - Precylia Ribka Rambing; Melky Krisna Paendong; Arief Perdana Kumaat; Romana Pessak (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
The large number of entrepreneurs in the field of selling fresh flowers in the city of Tomohon requires MSMEs to create unique and attractive products by implementing an innovation strategy in their business. By implementing innovations in fresh flower products, it is expected that MSMEs can produce products that have competitive advantages. This study aims to determine how much influence partially and simultaneously product innovation has on the competitive advantage of Ilomata fresh flower products. This research uses quantitative methods and uses a Likert scale as a measurement. The sampling technique uses a nonprobability sampling technique, namely purposive sampling technique. The population in this study were consumers of MSME Ilomata Tomohon fresh flower products, from this population there were 60 samples to be studied. The data analysis technique used in this study is multiple linear regression analysis. The results showed that partially the product innovation variable for each dimension had a significant effect because it had a t-count > t-table (2.004) and a significance level <0.05. Taken together the independent variable Product Innovation has a significant influence on the dependent variable Competitive Advantage with Fcount 12.692. The coefficient of determination is 67.7%, meaning that the influence of the product innovation variable on competitive advantage is 67.7%, while the remaining 32.3% is influenced by other variables not examined in this study.